Our Italian experience using lung ultrasound for identification, grading and serial follow‐up of severity of lung involvement for management of patients with COVID‐19. Issue 4 (15th April 2020) - Vetrugno, Luigi; Bove, Tiziana; Orso, Daniele; Barbariol, Federico; Bassi, Flavio; Boero, Enrico; Ferrari, Giovanni; Kong, Robert
Abstract: Lung ultrasound (LU) has rapidly become a tool for assessment of patients stricken by the novel coronavirus 2019 (COVID‐19). Over the past two and a half months (January, February, and first half of March 2020) we have used this modality for identification of lung involvement along with pulmonary severity in patients with suspected or documented COVID‐19 infection. Use of LU has helped us in clinical decision making and reduced the use of both chest x‐rays and computed tomography (CT).